Digital literacy in the European Union : a contribution to the state-of-the-art - Lisbôa, Eliana Santana (2012)
Digital Literacy is one of the skills needed to promote inclusion of people in the new social paradigm known as the Information Society. In the European case, inequalities in access to information are still noticeable and digital inclusion is still a subject of attention of the community policies authorities. In this communication we will start by examining the concept of literacy, and then we will discuss the concept of digital literacy which is not synonymous with technological equipping. It is much more than this, i.e., it’s about knowing to take advantage of the potential of information and communication technologies to form a responsible citizen in the twenty-first century, a citizen that is aware of the fact that digital inclusion is essential to promote the principles of lifelong learning in society.